Field assessment of the potentials of some plant-derived insecticide against damage caused by Leucinodes orbonalis on eggplant (Solanum gilo) at Umudike, Nigeria - Kingsley Chidi Emeasor; Nneka Fidel Nwahiri; David Nwazuo Enyiukwu (Universitas Lampung, 2022)
The efficacy of plant-derived insecticides was compared with a synthetic insecticide, Lambda-cyhalothrin over two cropping seasons (2015 and 2016) against Leucinodes orbonalis, the eggplant fruit and shoot borer (EFSB) infesting eggplant, Solanum gilo. The plant materials included oil palm (Elaeis guineensis) bunch ash, soursop (Annona muricata) seeds, and goat weed (Ageratum conyzoides) leaves. These plant materials were formulated into aqueous extracts of 150 g/L (w/v), while Lambda-cyhalothrin was applied at the rate of 5 mL/L (v/v). The experimental design was a Randomized Complete Block Design (RCBD). There were 5 treatments with 3 replications applied on 2 cultivars of eggplants (Afufa Ukwu and Ngwa Large). Percentage fruit damage varied significantly (P< 0.05) with various treatments. The lowest mean percentage fruit damage was observed in the plot treated with Lambda-cyhalothrin (20.38%), followed by goat weed (29.03%), soursop (40.69%), palm bunch ash (43.30%) and the control (67.08%) for 2015 and 2016. Other parameters measured followed the same trend. Mean yield was significantly affected by the treatments. The highest mean yield was obtained from the plots treated with Lambda-cyhalothrin (12,346.6 g), followed by plots treated with goat weed (11,295.0 g), soursop (9877.2 g), palm bunch ash (8729.4 g) and control was the least (6583.0 g). Among the plant extracts, A. conyzoides that recorded low mean percentage damage had very high yield. Therefore, it can be used as insecticides in the control of EFSB.